2009
DOI: 10.1016/j.ijsolstr.2009.08.023
|View full text |Cite
|
Sign up to set email alerts
|

The bending moment and springback in pure bending of anisotropic sheets

Abstract: a b s t r a c tFinite deformation rigid plastic and elastic-plastic analyses of plane strain pure bending of a plastically anisotropic sheet is presented. An efficient method for finding the exact solution is proposed by extending the previously developed method to the stage of unloading. Using this method the solutions are obtained in closed form or reduced to a numerical treatment of ordinary integrals, or an ordinary differential equation, or transcendental equations. An effect of plastic anisotropy and ela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…anelastic recovery) would result in inaccurate estimation of springback, as this has not often been considered in existing studies on springback reported in the literature [1,8,9,11] for different sample orientations. These results are in agreement with a number of studies evaluated the effects of anisotropic mechanical properties on springback [7,[28][29][30]. Therefore, it is imperative to consider materials anisotropic behaviour, to estimate springback accurately.…”
Section: Springback Characterisationsupporting
confidence: 89%
See 1 more Smart Citation
“…anelastic recovery) would result in inaccurate estimation of springback, as this has not often been considered in existing studies on springback reported in the literature [1,8,9,11] for different sample orientations. These results are in agreement with a number of studies evaluated the effects of anisotropic mechanical properties on springback [7,[28][29][30]. Therefore, it is imperative to consider materials anisotropic behaviour, to estimate springback accurately.…”
Section: Springback Characterisationsupporting
confidence: 89%
“…Few studies have attempted to take the anisotropic mechanical properties into an account when estimating springback [7,[28][29][30]. It was concluded that the springback magnitude was dependent on the orientation of the investigated sample with respect to the rolling direction of the original sheet.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been extended to a model of pressure-dependent plasticity in Lyamina [14] and a class of anisotropic materials in Alexandrov and Hwang [15]. Alexandrov and Hwang [15,16] have also extended the approach proposed in [13] to include the unloading stage and prediction of residual stresses. A somehow similar method for the stage of loading has been earlier proposed in [17].…”
mentioning
confidence: 99%
“…The theory of the elastic/plastic plane strain bending of an incompressible anisotropic sheet obeying the quadratic Hill yield criterion [12] has been presented in the article [13]. Ultimately, the main results of this work are represented in this section.…”
Section: Theory Of Bending At Large Strainmentioning
confidence: 99%